Theoretical and Experimental Study of Energy-Harvesting and Movement-Sensing Solutions in Pneumatic Systems - Monica Tiboni; Federico Scassola; Alessandro Zanacchi; Marco Ghidini (Sensors)
This paper presents an experimentally based study aimed at assessing the viability of employing a commercial energy harvester to develop a self-powered end-stroke and speed sensor for pneumatic cylinders. An energy-harvesting device was integrated into a cylinder end-cap to recover energy from the piston impact at the end of the stroke. The recovered energy powers a radio transmitter that communicates the reach of the end-stroke. This avoids the use of a dedicated end-stroke sensor, reducing the number of components in the system and also saving energy. The experiments aimed to analyze the signal characteristics generated by the module at various activation speeds, assessing whether the impact speed could be distinguished from the signal. Energy output and short-term usage effects were also investigated. The study seeks to further develop and adapt a Simulink model of the system, based on recent studies, and validate it with experimental findings at the tested activation speeds. Following confirmation of the adapted model’s validity, the authors propose using genetic algorithms to design an optimized mechanical energy harvester. This approach aims to find the parameters of an energy harvester more suitable for pneumatic cylinder applications that would enable enhanced energy extraction and overall improved performances.